The Everlasting Plague of Settler Colonialism in South Africa: An Autoethnographic Study on the Settler Logic of Eliminations? Assimilative Projects and its Impact Upon Understandings of Identity and the Self - Mohedeen, Alia (Department of Political Studies, 2024)
Eyewitness testimonies are integral pieces of evidence in criminal justice investigations. This is because justified conviction and appropriate sentencing can flow from eyewitness testimony. However, research has demonstrated that eyewitness testimony is often unreliable, even more so, the testimony of eyewitnesses who have witnessed multiple perpetrator crimes. This is because eyewitnesses to multiple perpetrator crimes have the challenging tasks of recalling the crime scene, correctly identifying the perpetrators involved in the crime, and assigning the correct role to each perpetrator. Eyewitnesses in the current study viewed a mock crime video comprising one, two, or five perpetrators and were instructed to answer a number of crime-related questions and identify the perpetrator/s from the line-up. The line-ups were presented sequentially (with one perpetrator in each line-up) for eyewitnesses who viewed the multiple perpetrator crimes. Additionally, these eyewitnesses were required to pair each perpetrator to the role they played in the crime. Analysis of the sample (N = 226) revealed that the accuracy of eyewitnesses decreased as the number of perpetrators increased. The ‘post-identification feedback' effect has not yet been studied in multiple perpetrator crimes. Single perpetrator research demonstrates that any suggestion that the eyewitness chose the correct person from the line-up inflates eyewitness confidence. We hypothesized that the effect would also persist in eyewitnesses who viewed multiple perpetrator crimes. We analysed 1991 of the 226 eyewitnesses and found that postidentification feedback did not significantly affect eyewitness identification and role confidence